Emergy Evaluation of Domestic Wastewater Treatments: The Role of Energy and Materials Consumption and Carbon Emissions - Giannetti, B.F.; Silva, C.C.; Agostinho, F.; Almeida, C.M.V.B. (Journal of Environmental Accounting and Management, 2026)
Technologies for domestic wastewater treatment systems can be planned and constructed to use locally available materials lessening the need for resupply materials and to fit the local conditions. However, most plans for wastewater treatment systems do not consider the renewable support required to dilute plants’ emissions. Solutions for mitigating environmental impacts and achieve sustainable environments with low carbon depend on the accounting for the available local resources and the environmental services required for diluting emissions. Two example applications of domestic wastewater treatment metabolism are discussed using sustainability indicators and inputs to the greenhouse gas emissions calculation. The analysis compares upstream and downstream environmental investments and may be used to advise public policies for sustainable regional and urban development.